The art of stage-craft: A dramaturgical perspective on strategic change. (November 2021) - Whittle, Andrea; Gilchrist, Alan; Mueller, Frank; Lenney, Peter
This article contributes to our understanding of how organisations change the set of practices and practitioners involved in strategising, what we term the 'strategy arrangement'. Drawing on insights from a qualitative study of the introduction and subsequent removal of a new strategy team, we develop a dramaturgical theory of the practices involved in changing strategy arrangements. First, we conceptualise the relationship between the frontstage performances where impressions are generated and the backstage work that takes place to craft and control those impressions. Second, we distinguish between preventive practices designed to 'stage the show', where foresight is used to imagine the impressions of the audience and inform the design of the show, and corrective practices designed to 'save the show', where the desired impression has been discredited and repair is needed to restore the desired impression. Third and finally, we distinguish between the more innocuous backstage practice of rehearsing, the 'behind the scenes' work that involves taking up the roles of actor, playwright, director, audience and critic to craft the show, and the less innocuous practice of conspiring, where team members work 'behind the backs' of the audience to construct false impressions. In so doing, we seek to advance strategy-as-practice research by developing a dramaturgical theory of practice that captures the theatrical dynamics of strategic change.